Hydrophosphination as a valuable tool to chiral diphosphines and their derivatives - Teo, Ronald Hong Xiang (Nanyang Technological University, 2022)
Chiral diphosphine ligands are a ubiquitous class of privileged ligand which finds extensive application in transition metal catalysis and biochemistry. This thesis explores the development of a new methodology of accessing P-chiral diphosphine ligands with high to excellent enantioselectivities and moderate diastereoselectivities. Next, the synthesis of C-chiral diphosphines from naturally occurring curcumin and derivatives was attempted and the cytotoxicity of the diphosphine metal complexes was evaluated and compared against cisplatin and curcumin in the MKN74 and MCF7 cancer cell-lines. Lastly, the challenges associated with the generation of chiral phosphine-phosphino-chalcogenide and their complexes were discussed in detail and an example of the catalytic property of the phosphine-phosphino-chalcogenide metal complexes was illustrated.